A digital flora of Rome. (3rd May 2016) - Nimis, P. L.; Moro, A.; Attorre, F.; Martellos, S.; Chiancone, E.
Abstract: A complete guide to the rich flora of the metropolitan area of Rome (more than 1600 infrageneric taxa) was made available both as an online multi-entry query interface and as a stand-alone dichotomous key for mobile devices. From the general key, it will be possible to derive many smaller (and hence easier) guides to different parks and gardens of Rome, while teachers have been provided with additional software which permits them to create their own keys for any subset of species.